The Experimental Study of an SPWM-Based Controller in an Inverter - Ahmad Kamal, Muhammad Daniel; Yahaya, Jabbar Al-Fattah (Evolution in Electrical and Electronic Engineering, 2025)
This project tends to design and implement an SPWM inverter to provide a stable AC output with low THD value according to IEEE 1547 standards for applications in solar power systems. MATLAB/Simulink checks the efficiency at different loads and frequencies and incorporates a modified MPPT charge controller for a stable input. This chapter presents the design and application of a solar power system with an AC source for a load. This isotype needs a solar panel, boost converter, MPPT charger, and Arduino operated SPWM inverter/LC filter/MCCB in it. Tasks include system design, MATLAB Simulink, integration of hardware components, and cobbling up of the system in C-code, with strong consideration of feedback control, debugging, and confirmation of the system. This project proposes and implements the design, simulation, and realization of a solar-powered SPWM inverter intended for AC loads. MATLAB Simulink was used to ensure proper characterization of design parameters, best waveform quality, and reduced THD. As tested, the hardware output was stable at different frequencies and voltages, following the specified IEEE standards and offering reliable performance for clean sinusoidal AC power production. Constructed using the SPWM technique, this solar inverter project generated a clean, stable AC with a low THD, as confirmed by MATLAB Simulink and the actual hardware. Under conditions of variable load and frequency, in compliance with IEEE 1547 standards, the system was effective, stable, and capable of small-scale renewable energy applications and supply of single-phase AC loads such as household appliances.